A Rare Case of Dermatomyositis Sine Dermatitis in an Indian Geriatric Patient - Saumyarup Pal; Akshata Rao; Abhijith R. Rao; Bhabhor Kaminiben Narsinhbhai; Mujtaba Waris; Saumya Sahu; Avinash Chakrawarty (Journal of the Indian Academy of Geriatrics)
Dermatomyositis sine dermatitis (DMSD) is a rare form of dermatomyositis (DM). They present with subacute to chronic symmetrical proximal muscle weakness, with a female preponderance. It is distinguished from classical DM by the absence of typical skin manifestations. We present a rare case of DMSD in a 65-year-old male patient who had an atypical presentation of subacute swelling and proximal muscle weakness of bilateral upper limbs followed by lower limbs, associated with pain, frailty, and dependency for daily activities. The diagnosis of DMSD was based on the typical muscle biopsy findings in the absence of any skin manifestations aided by elevated muscle-related enzymes, and myopathic patterns on electromyography. The screening was negative for muscle-specific antigens, malignancy, and extra muscular involvement. Pulse steroid therapy followed by gradual tapering, methotrexate, and regular physiotherapy significantly improved functionality.